Progression of nephropathy after islet of langerhans transplantation in alloxan-induced diabetic rats - Spadella,César Tadeu (1997)
We studied the effects of islet of Langerhans transplantation (IT) on the kidney lesions of rats with alloxan-induced diabetes. Forty-five inbred male Lewis rats were randomly assigned to 3 experimental groups: group Gl included 15 non-diabetic control rats (NC), group GIT included 15 alloxan-induced diabetic rats (DC), and group III included 15 alloxan-induced diabetic rats that received pancreatic islet transplantation prepared by nonenzymatic method from normal donor Lewis rats and injected into the portal vein (IT). Each group was further divided into 3 subgroups of 5 rats which were sacrificed at 1, 3, and 6 months of follow-up, respectively. Clinical and laboratorial parameters were recorded in the mentioned periods in the 3 experimental groups. For histology, the kidneys of all rats of each subgroup were studied and 50 glomeruli and 50 tubules of each kidney were analyzed using light microscopy by two different investigators in a double blind study. The results showed progressive glomerular basement membrane thickening (GBMT), mesangial enlargement (ME), and Bowman's capsule thickening (BCT) in the 3 experimental groups throughout the follow-up. These alterations were significantly more severe in DC rats at 6 months when compared to NC rats (p < 0.01). However, the degree of GBMT, ME, and BCT observed in DC rats was not statistically different from IT rats at 1, 3, and 6 months. In addition, Armanni-Ebstein lesions of the tubules (AE) and tubular lumen protein (PRO) observed in DC rats were also observed in IT rats all over the study. These lesions were never present in NC rats. We conclude that IT did not prevent progression of kidney lesions in alloxan-induced diabetic rats within 6 months after transplantation.